Providing Relevant Teacher Education To Teachers of Inclusive Education in Primary Schools in Eswatini - Shongwe, Elmon Jabulane (Edukasiana: Jurnal Inovasi Pendidikan, 2024)
The study aims to investigate the appropriateness of teacher education provided by teacher training institutions to teachers for an inclusive set-up in primary schools, Eswatini. Learners with disabilities in Eswatini are usually found in special schools; however, the government of Eswatini advises parents to send these children to nearby community schools. The study investigated whether the teachers in public primary schools were appropriately trained by the teacher training institutions for inclusive classrooms. A qualitative approach was used in the study, employing the multiple case study design. Semi-structured interviews were used to collect data from Eswatini senior inspector of inclusive education, a parent of an out-of-school child with a disability, two teachers and a school principal from each of the four schools involved in the study. The recommendations would assist teacher training institutions in Eswatini to improve inclusiveness in their courses. The study revealed that teachers were not competent to teach learners with disabilities in an inclusive classroom. Some primary schools did not admit children with disabilities due to their pre-service training.  The study recommended that the pre-service training should be aligned with the situations in schools. Through the study, a model ensuring teachers' competence in inclusive education was produced.